2020
DOI: 10.1158/1940-6207.capr-19-0422
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Upper Gastrointestinal Cancer Screening in a Randomized Controlled Trial: Baseline Results in a Non-high-incidence Area

Abstract: A cluster-randomized controlled trial (RCT) was conducted to evaluate to the effectiveness of reducing mortality of upper gastrointestinal cancer (UGC) and feasibility of screening through a questionnaire combined with endoscopy in non-high-incidence urban areas in China. The trial design, recruitment performance, and preliminary results from baseline endoscopy are reported. Seventy-five communities in two urban cities with a nonhigh-incidence of UGC were randomized to a screening endoscopy arm (n ¼ 38) or a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The detailed requirements see our previous study. 16 We freely provided to subjects for normal endoscopy performed under without anesthesia.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
See 3 more Smart Citations
“…The detailed requirements see our previous study. 16 We freely provided to subjects for normal endoscopy performed under without anesthesia.…”
Section: Endoscopic Screeningmentioning
confidence: 99%
“…Within China, striking geographic variations exist in the incidences of UGC, which can vary more than 10‐fold in different regions 14,15 . Hunan province, as non‐high‐incidence area, also stated this program at 2012 with serious disease burden of UGC 16 . Our previous cluster randomized trial showed that the questionnaire evaluation could not effectively concentrate the UGC high‐risk individuals 16 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, the detection rate of early UGI tract cancer, with conventional esophagogastroduodenoscopy, remains low [ 9 ]. Although new online learning platforms have been introduced to help gastroenterologists to master their diagnostic skills in endoscopic detection of early UGI tract disease and to allow for more favourable outcomes [ 10 ], the roll-out of mass-screening is difficult and often hampered by a relatively low compliance rate [ 11 ]. Furthermore, meta-analyses demonstrated that around 10% of UGI cancers are missed during endoscopy exams performed within 3 years before diagnosis [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%